„Folosul de obşte” sau despre umanismul baroc - Dan Horia Mazilu (Revista de Istorie și Teorie Literară)
The article discusses the concept of “common use” („folosul de obşte”) in the Romanian Literature of the Baroc age. The concept is a legacy of the Renaissance and the main meaning is that of an ethic and educational goal.